Drug use study recommended for agricultural storage for guinea pigs farms in pasto city, colombia (2012)
Objective. To identify the main drugs recommended by agricultural stores to the guinea pigs(Cavia porcellus) farms in the municipality of Pasto (Colombia). Materials and methods. Patterns of drug use in 30 agricultural stores where characterized through a survey. Data were analyzed with the help of statistical software Statgraphics Plus 5.0. Results. Descriptive statistics indicated that enrofloxacin is the most recommended drug (24.54%), the drug doses recommended where 1.2 to 40 mg in adult animals and 0.8 to 40 mg in young animals, followed by ivermectin (23.93%), the drug doses recommended where 200 to 500 mcg in adult animals and 100 to 500 mcg in young animals and fenbendazole (21.37%) the drug doses recommended where 15 to 100 mg in adult animals and 5 to 100 mg in young animals. Conclusions. A lack of compliance with the regulations for prescription drugs in agricultural stores is observed. Most medications are used outside therapeutic ranges. The drug groups most recommended by agricultural stores are antiparasitics (64.95%) and antibiotics (35.04%).